Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1124/jpet.104.065425
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin-II-Converting Enzyme Activity of Furin and Trypsin in Human Cells in Vitro

Abstract: Human urotensin-II (hU-II) is processed from its prohormone (ProhU-II) at putative cleavage sites for furin and serine proteases such as trypsin. Although proteolysis is required for biological activity, the endogenous "urotensin-converting enzyme" (UCE) has not been investigated. The aim of this study was to investigate UCE activity in cultured human cells and in blood, comparing activity with that of furin and trypsin. In a cell-free system, hU-II was detected by high-performance liquid chromatography-mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…The mature peptide UII results from the proteolysis of preproprotein UII at the tribasic site KKR by a specific urotensin converting enzyme (UCE), which is not still identified (4, 5). Study on the conversion of a 25 amino acid C-terminal fragment of preproprotein to mature peptide revealed that the endoprotease Furin and the serine protease trypsin, may act, respectively, as intracellular and extracellular UCE (12). This enzymatic cleavage appears necessary to confer biological activity (13).…”
Section: The Uii Peptide Systemmentioning
confidence: 99%
“…The mature peptide UII results from the proteolysis of preproprotein UII at the tribasic site KKR by a specific urotensin converting enzyme (UCE), which is not still identified (4, 5). Study on the conversion of a 25 amino acid C-terminal fragment of preproprotein to mature peptide revealed that the endoprotease Furin and the serine protease trypsin, may act, respectively, as intracellular and extracellular UCE (12). This enzymatic cleavage appears necessary to confer biological activity (13).…”
Section: The Uii Peptide Systemmentioning
confidence: 99%
“…3), with a molecular weight of ~1,388 (32). This peptide, isolated originally from fish urophysis (a neurosecretory organ of the caudal spinal cord), is derived from pre-pro U-II, which consists of 124 and 139 amino acid residues, by urotensinconverting enzyme (33). U-II has been identified as an endogenous ligand for the G-protein coupled receptor 14 (GPR14)/ sensory epithelia neuropeptide-like receptor (SENR) orphan receptor, with seven transmembrane domains, which was cloned recently and renamed the UT receptor (34).…”
Section: U-ii and Ut Receptor Systemmentioning
confidence: 99%
“…2), with a molecular weight of ~1388 [22]. This peptide is derived from pre-pro U-II, consisting of 124 and 139 amino acid residues, by urotensin-converting enzyme [23]. U-II has been identified as an endogenous ligand for an orphan receptor G-protein coupled receptor 14 (GPR14), with seven transmembrane domains, which was cloned recently and renamed UT receptor [24].…”
Section: U-ii and Ut Receptor Systemmentioning
confidence: 99%